2001
DOI: 10.1002/1521-3773(20011203)40:23<4417::aid-anie4417>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

From Cyclodextrin Assemblies to Porous Materials by Silica Templating We thank the Max-Planck society for funding.

Abstract: Self‐organization in aqueous media studied indirectly: The aqueous phase is solidified by a silica sol–gel process, and the supramolecular aggregate is 1:1 cast into a solid silica matrix. For the model‐system cyclodextrins it was shown that the cyclodextrin molecules self‐assemble into “wormlike” aggregates in the porous silica (see scheme). By using this template, porous materials were obtained with promising properties such as a uniform pore system and smooth walls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
122
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(128 citation statements)
references
References 44 publications
6
122
0
Order By: Relevance
“…84 Cyclodextrins are cyclic sugars containing 6 (a-), 7 (b-), or 8 (g-CD) glucose units 1,4-cyclically connected to a 'molecular barrel'. It is known from the literature 85 that these 'barrels' have an exterior which is covered by OH-groups while the interior cavity is quite hydrophopic, characterized by CH 2 groups.…”
Section: Cyclodextrins As Templatesmentioning
confidence: 99%
“…84 Cyclodextrins are cyclic sugars containing 6 (a-), 7 (b-), or 8 (g-CD) glucose units 1,4-cyclically connected to a 'molecular barrel'. It is known from the literature 85 that these 'barrels' have an exterior which is covered by OH-groups while the interior cavity is quite hydrophopic, characterized by CH 2 groups.…”
Section: Cyclodextrins As Templatesmentioning
confidence: 99%
“…The CDs compound has a truncated cone shape. It has been reported that cyclodextrins can act as templates for the production of porous silica materials with pore size closely corresponding with the cyclodextrin diameters (1.5-2 nm) and bicontinuous ''worm-type'' pore structures using a nanocasting concept [12]. On the other hand, MCM-41 having a 3-to 10-nm-sized pore with a hexagonal crystalline pore structure has been reported.…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that these fiber assemblies were formed by assembling CD molecules in a channel fashion. The driving force for the formation of these self-assemblies can be ascribed to hydrogen bonding interactions between the hydroxyl groups of the CDs (26,(30)(31)(32)(33). The formation of these assemblies was inhibited by chemical modification of the hydroxyl groups of the CDs, the addition of hydrogen-bond-disrupting agents such as urea, and the ionization of the CD hydroxyl groups by increasing the pH of the solutions to above pH 12.…”
Section: Formation Of Cyclodextrin Assemblies In Aqueous Solutionmentioning
confidence: 99%